ANALISIS SIKAP, LOYALITAS, DAN FAKTOR-FAKTOR YANG MEMENGARUHI PEMBELIAN MINYAK GORENG KEMASAN BIMOLI DAN SANIA DI PASAR TRADISIONAL DI KOTA BANDAR LAMPUNG - Roylando P Togatorop; Dyah Aring Hepiana Lestari; Wuryaningsih Dwi Sayekti (Lampung University, 2022)
This study aims to determine consumers’ attitudes and the factors that influence purchasing of Bimoli and Sania cooking oil packaging at markets in Bandar Lampung. This research was conducted at five markets namely Rakyat Tani, Tempel Waykandis, Waykandis, Tempel Cahaya, and Tempel Gotong Royong. The number of consumer respondents was 60 people, recruited accidentally. Research data were analyzed using multiatribute Fishbein and multiple linear regression. Consumers’ attitude showed that the Bimoli brand and Sania cooking oil packaging got the highest scores. Consumers’ purchasing of Bimoli cooking oil packaging was influenced by the price of Bimoli cooking oil packaging, family income, and family members. Consumers’ purchasing Sania cooking oil packaging was influenced by the price of Sania cooking oil packaging, the price of bulk cooking oil, the price of Tropical cooking oil packaging, and the price of Kunci Mas cooking oil packaging. Key words: attitudes, consumers’ purchasing, cooking oil packaging